History and Public Memory in Tobago: Opportunities and Obstacles. Issue 375 (8th February 2022) - Joseph, O'Neil
Abstract: Since the 1980s, policymakers on the island of Tobago positioned public history as one of the main pillars for sustainable economic and social development. As such, from the early 1980s public history became central to the island's development policy and planning. Locals, researchers and tourists consume and experience public history at sites of memory throughout the island. This article contends that while sites of memory in Tobago provide unprecedented opportunities for Tobagonians, the heritage and tourism sectors and researchers; these sites are complicated by government policies, tropical tourism narratives, emotional investments and competing groups aims, all of which pose major obstacles.